New method to measure domain‐wall motion contribution to piezoelectricity: the case of PbZr0.65Ti0.35O3 ferroelectric. Issue 4 (24th July 2020) - Gorfman, Semën; Choe, Hyeokmin; Zhang, Guanjie; Zhang, Nan; Yokota, Hiroko; Glazer, Anthony Michael; Xie, Yujuan; Dyadkin, Vadim; Chernyshov, Dmitry; Ye, Zuo-Guang
Abstract : A new single‐crystal X‐ray diffraction method and data analysis framework have been developed and implemented for the separation of intrinsic and domain‐wall‐motion contributions to the piezoelectric effect in functional ferroelectric materials. The technique is applied for the elucidation of the mechanism of piezoelectricity in a single crystal of the ferroelectric PbZr0.65 Ti0.35 O3 . Abstract : A new data analysis routine is introduced to reconstruct the change in lattice parameters in individual ferroelastic domains and the role of domain‐wall motion in the piezoelectric effect. Using special electronics for the synchronization of a PILATUS X‐ray area detector with a voltage signal generator, the X‐ray diffraction intensity distribution was measured around seven split Bragg peaks as a function of external electric field. The new data analysis algorithm allows the calculation of `extrinsic' (related to domain‐wall motion) and `intrinsic' (related to the change in lattice parameters) contributions to the electric‐field‐induced deformation. Compared with previously existing approaches, the new method benefits from the availability of a three‐dimensional diffraction intensity distribution, which enables the separation of Bragg peaks diffracted from differently oriented domain sets. The new technique is applied to calculate the extrinsic and intrinsic contributions to the piezoelectricity in a single crystal of the ferroelectric PbZr1− x Ti x O3 ( x = 0.35). The root‐mean‐square value of the piezoelectric coefficient was obtained as 112 pC N −1 . The contribution of the domain‐wall motion is estimated as 99 pC N −1 . The contribution of electric‐field‐induced changes to the lattice parameters averaged over all the domains is 71 pC N −1 . The equivalent value corresponding to the change in lattice parameters in individual domains may reach up to 189 pC N −1 .